Pengembangan Video Animasi Vtuber pada Pembelajaran Bahasa Indonesia Siswa SMP Kelas VIII Tahun Pelajaran 2022/2023 - Sobri, Sobri; Hilaliyah, Tatu; Zahra, Aini (Universitas Mathla'ul Anwar Banten, 2023)
This study aims to describe the steps for developing Vtuber animated video learning media, test the feasibility of media for use, and students' responses to media. This research is a part of research and development (R&D) using the multimedia development method proposed by Luther based on 6 stages of development. The data collection techniques carried out are interviews, questionnaires, and documentation. The subjects in this study were students of classes VIII A and VIII B of SMP Negeri 9 Serang City. Data analysis was carried out using descriptive statistical techniques. Media experts and material experts carry out validation tests to determine the feasibility of the media. The results showed that the Vtuber interactive animated video learning media received a percentage score of 82.5% with the criteria